Enhancing order management with ERP systems: A case study in a subcontractor company - Sing, Jason Fung Chee; Lee, Khai Loon (Penerbit Universiti Malaysia Pahang, 2023)
The construction industry is constantly evolving and that affects the timeline of order, plus the requirement of clients have become more complicated. The report from the construction district showed that the delay in projects was due to various reasons, mainly because of clients and consultants. This study focuses on order management, as this department directly affects the company performance and client satisfaction. Therefore, it is important to study and improve the order management process. This study intended to understand the order management processes and determine the challenges and the root cause of delay in the order management department. In this case study, a series of interviews have been conducted with a representative of the ABC Engineering Sdn Bhd. A semi-structured interview protocol is used to support the interview. With the consensus of the interviewee, the discussions are recorded for transcript and data analysis purposes. This study identified the processes of order management and found that the project delay is mainly due to poor and ineffective communication between departments in the company when there is a change of client requirement. From the findings of order management processes, challenges, and root causes of the problem, this study proposes Epicor Enterprise Resource Planning (ERP) system to enhance the order management of ABC Engineering Sdn Bhd. The system is proposed because the company has the existing talent in the company for implementation and execution. This study believed that the implementation of the Epicor system with reinforcement in the company could help in minimizing the reoccurring problem of delay.